Hydrodeoxygenation of phenolics over uniformly dispersed Pt–Ni alloys supported by self–pillared ZSM–5 nanosheets. (15th August 2022) - Guo, Longhui; Tian, Yajie; He, Xinyu; Qiao, Congzhen; Liu, Guozhu
Highlights: Bimetallic Pt–Ni was supported on self–pillared nanosheet ZSM–5(SP) by impregnation. Adsorption of phenolics increased with highly exposed surface areas of SP. Highly distributed Pt–Ni alloy promoted the adsorption and spillover of hydrogen. Pt–Ni/SP gave excellent HDO performance of anisole and guaiacol. Abstract: Zeolite supported transition metal catalysts have been proved highly efficient for hydrodeoxygenation (HDO) of bio–oil, but always faced decreased catalytic activity due to the aggregations of metal cluster and the restricted diffusion by only microporous zeolite. In this work, Pt–Ni bimetals supported on a self–pillared nanosheet ZSM–5 zeolite catalyst (Pt–Ni/SP) was prepared by wetness impregnation. The Pt–Ni/SP catalyst with highly exposed surface areas improved the dispersion of Pt–Ni alloy on the carrier surface with the establishment of strong metal–support interaction, after sequenced calcination and reduction. The promoted adsorption and spillover of active hydrogen were realized by the Pt–Ni/SP catalyst, thus giving an enhanced HDO of phenolics, than the monometallic Ni/SP and Pt/SP catalysts. Moreover, the adsorption of phenolics was promoted, due to the hierarchical structure. Pt–Ni/SP catalyst show significant higher catalytic conversion of anisole and guaiacol than the bimetallic catalyst using commercial microporous ZSM–5 as support (Pt–Ni/CZ), through sequenced hydrogenation and deoxygenation procedures.